2004
DOI: 10.1038/sj.ejhg.5201314
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in the known genes are not the major cause of MED; distinctive phenotypic entities among patients with no identified mutations

Abstract: Multiple epiphyseal dysplasia (MED) is a clinically and genetically heterogeneous chondrodysplasia. Mutations in six genes (COMP, COL9A1, COL9A2, COL9A3, MATN3 and DTDST) have been reported, but the genotype -phenotype correlations and the proportions of cases due to mutations in these genes are still not well characterized. We performed a clinical, radiological and molecular analysis of known MED genes on 29 consecutive MED patients. The mutation analysis resulted in identification of the DTDST mutation in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…This detection rate is higher than those reported in comparable studies of Western populations [Briggs and Chapman, 2002;Jakkula et al, 2003;Jackson et al, 2004;Jakkula et al, 2005]. The increased rate may result from the analysis method used; in previous studies, most COMP and type IX collagen genes were screened using conformation sensitive gel electrophoresis, or only limited regions of each gene were examined.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This detection rate is higher than those reported in comparable studies of Western populations [Briggs and Chapman, 2002;Jakkula et al, 2003;Jackson et al, 2004;Jakkula et al, 2005]. The increased rate may result from the analysis method used; in previous studies, most COMP and type IX collagen genes were screened using conformation sensitive gel electrophoresis, or only limited regions of each gene were examined.…”
Section: Discussionmentioning
confidence: 59%
“…This algorithm can improve the efficiency of genetic analysis for MED, but the unidentified gene(s) that account for as many as half of MED cases still present a challenge. The absence of known gene mutations despite our complete sequence analysis of these genes indicates the existence of additional MED gene(s), which is also supported by linkage analysis [Jakkula et al, 2005]. Identification of new MED gene(s) will help refine the strategy for genetic analysis of MED patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In an early study on Caucasian population reported the proportions of DTDST as 14%, COMP as 10%, MATN3 as 10%, and unknown as 66% in 29 MED patients [7]. Subsequent studies reported that COMP (47% and 50%) was the most common causative gene followed by DTDST (25% and 28%), while MATN3 (17%) and COL9A1, 2, and 3 (8%) comprised only a small portion of these MED patients [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, further identification of unknown MED genes is necessary for this system. Known gene mutations were found in fewer than half of the MED patients (Jackson et al 2004;Jakkula et al 2005). Familial cases not linked to known MED loci exist (Jakkula et al 2005; our unpublished experience).…”
Section: Genetic Diagnosis Of Skeletal Dysplasiamentioning
confidence: 99%